ISBAT NIKAH PASANGAN DI BAWAH UMUR DI PENGADILAN AGAMA PURWAKARTA - Hanif Fauzi (Asy-Syari'ah, 2021)
Abstract: Marriage ratification or itsbat nikah is a way out for unregistered marriages in order to obtain registration and recognition from the state. Not every application for ratification of marriage is always granted, sometimes the application is rejected which refers to the Compilation of Islamic Law. This paper has the aim of revealing the basis for the judge's considerations as well as having a role as chairman of the Purwakarta Religious Court when processing several cases regarding the legalization of underage marriages which always grants and never rejects the application, this is interesting because there is a decision by another Religious Court judge who refuses similar application. This study uses this analysis method (content analysis) with a qualitative approach. The results of this study show that the judge in question concluded that the age of the bride and groom is not a benchmark for accepting or rejecting the application for itsbat marriage, but the parameter is that every marriage that meets the conditions and pillars is legal and worthy of marriage, but unfortunately the conclusion is not attached to the sheet. the decision and give the impression that it is very easy to apply for an istbat. Therefore, underage marriages as long as they fulfill the pillars and requirements are treated as legal marriages and will always be accepted and granted the application for ratification of marriage.Absktrak: Pengesahan nikah atau itsbat nikah merupakan jalan keluar bagi pernikahan yang tidak tercatat demi mendapatkan pencatatan dan pengakuan dari negara. Tidak setiap permohonan pengesahan nikah itu selalu dikabulkan, adakalanya permohonan itu ditolak yang mengacu pada Kompilasi Hukum Islam. Tulisan ini bertujuan untuk mengungkapkan dasar landasan pertimbangan hakim sekaligus memiliki peran sebagai ketua Pengadilan Agama Purwakarta ketika menangani beberpa perkara tentang pengesahan nikah perkawinan anak di bawah umur yang selalu mengabulkan dan tidak pernah menolak permohonan tersebut, hal ini menarik karena adaya putusan hakim Pengadilan Agama lain yang menolak permohonan yang serupa. Penelitian ini menggunakan metode analisis ini (content analysis) dengan pendekatan kualitatif. Hasil penelitian ini menunjukan bawa hakim yang bersangkutan memberikan kesimpulan bahwa usia pengantin bukanlah patokan untuk menerima atau menolak permohonan itsbat nikah, melainkan parameternya adalah setiap perkawinan yang  terpeuhi syarat dan rukunya itu adalah sah dan layak untuk diistbatkan, namun sangat disayangkan ungkapan tersebut tidak dilampirkan dan dituliskan secara jelas dalam setiap lembaran putusan yang memerikan kesan bahwa hakim sangat mempermudah sekali untuk mengabulkan istbat. Oleh karena itu pernikahan dibawah umur selama memenuhi rukun dan syarat dininai sebagai perkawinan yang san dan akan selalu diterima dan dikabulkan permohonan pengeshan nikahnya di Pengadilan Agama Purwakarta.